Comparison of the fixation ability of headless compression screws and locking plate for metacarpal shaft transverse fracture. Issue 39 (1st October 2021) - Chiu, Yung-Cheng; Hsu, Cheng-En; Ho, Tsung-Yu; Ting, Yen-Nien; Wei, Bor-Han; Tsai, Ming-Tzu; Hsu, Jui-Ting
Abstract : Abstract: Metacarpal shaft fractures are common hand fractures. Although bone plates possess strong fixation ability, they have several limitations. The use of headless compression screws for fracture repair has been reported, but their fixation ability has not been understood clearly. This study aimed to compare the fixation ability of locked plate with that of headless compression screw for metacarpal fracture repair. A total of 14 artificial metacarpal bones (Sawbones, Vashon, WA, USA) were subjected to transverse metacarpal shaft fractures and divided into 2 groups. The first group of bones was fixed using locked plates (LP group), whereas the second group was fixed using headless compression screws (HC group). A material testing machine was used to perform cantilever bending tests, whereby maximum fracture force and stiffness were measured. The fixation methods were compared by conducting a Mann–Whitney U test. The maximum fracture force of the HC group (285.6 ± 57.3 N, median + interquartile range) was significantly higher than that of the LP group (227.8 ± 37.5 N; P < .05). The median of the HC group was 25.4% greater. However, no significant difference in stiffness ( P > .05) was observed between the HC (65.2 ± 24.6 N/mm) and LP (61.7 ± 19.7 N/mm) groups. Headless compression screws exhibited greater fixability than did locked plates, particularly in its resistance to maximum fracture force.